Nano-enabled agrochemicals/materials: Potential human health impact, risk assessment, management strategies and future prospects. (15th February 2022) - Okeke, Emmanuel Sunday; Ezeorba, Timothy Prince Chidike; Mao, Guanghua; Chen, Yao; Feng, Weiwei; Wu, Xiangyang
Abstract: Nanotechnology is a rapidly developing technology that will have a significant impact on product development in the next few years. The technology is already being employed in cutting-edge cosmetic and healthcare products. Nanotechnology and nanoparticles have a strong potential for product and process innovation in the food industrial sector. This is already being demonstrated by food product availability made using nanotechnology. Nanotechnologies will have an impact on food security, packaging materials, delivery systems, bioavailability, and new disease detection materials in the food production chain, contributing to the UN Millennium Development Goals targets. Food products using nanoparticles are already gaining traction into the market, with an emphasis on online sales. This means that pre- and post-marketing regulatory frameworks and risk assessments must meet certain standards. There are potential advantages of nanotechnologies for agriculture, consumers and the food industry at large as they are with other new and growing technologies. However, little is understood about the safety implications of applying nanotechnologies to agriculture and incorporating nanoparticles into food. As a result, policymakers and scientists must move quickly, as regulatory systems appear to require change, and scientists should contribute to these adaptations. Their combined efforts should make it easier to reduce health and environmental impacts while also promoting the economic growth of nanotechnologies in the food supply chain. This review highlighted the benefits of a number of nano enabled agrochemicals/materials, the potential health impacts as well as the risk assessment and risk management for nanoparticles in the agriculture and food production chain.